(untitled) (Nigerian Journal of Technology, 2002)
Using locally available materials, we have successfully constructed a pyranometer. This pyranometer has been calibrated against a standard Eppley pyranometer at the University of Nigeria, Nsukka and then used in measurement of intensity of solar radiation in Enugu which lies on latitude 6.200N– and longitude 7. 30oE. The investigation was carried out between October and December 1984. Our investigations show that the maximum mean instantaneous insolation for the months of October November and December in Enugu were 565.6 Wm-2 , 600.6 Wm-2 and 580.4 Wm -2 respectively. The maximum instantaneous insolation for the period usually occured between 11.30 a.m. and 1.00 p.m. Our results also reveal that the sudden appearance of harmattan haze drastically reduced the mean hourly insolation. These results compare favourably with similar investigations using other techniques.